Formation of Critical Concentrations of Natural Gas at its Leakage - Tulach, Ales; Mynarz, Miroslav; Kozubkova, Milada (Communications - Scientific Letters of the University of Zilina, 2015)
Spreading of natural gas during its leak from a domestic low pressure pipeline in a confined space is a complicated issue depending on many factors. In relation to possible explosion, created dangerous concentrations could be identified effectively by numerical simulations using mathematical CFD models. It is suitable to verify the results of numerical simulations by real experiment, even if it is a simplified one. Verified mathematical model could then offer detail picture of spreading of gas in a whole focused space. In executed numerical analysis, several mathematical models of gas flow were applied and they were compared to the results of experimental measurements. This paper deals also with formation and propagation of critical concentrations of natural gas in the whole observed space in the cubical experimental chamber. All above-mentioned matters could be applied in the fields dealing with safety of persons, technologies and objects, and it could be also used for explanation of accidents related to leakage and explosion of gas.
Keywords: CFD models; leakage of gas; propagation of gas; natural gas; dangerous concentration; explosive concentration